Trauma emocional y su repercusión en la conducta de un joven de 20 años de la ciudad de Babahoyo - Garzón Morales, Mirian Cecilia (2023)
This case study on emotional trauma and its impact on the behavior of a 20-year-old young adult from the city of Babahoyo focuses on the way in which a car accident affects the patient's behavior and how she feels about it. to this affectation both at the cognitive, affective, behavioral and somatic level. Given the symptoms, the individual feels guilty, has repetitive thoughts, irritable behavior, and also has nightmares about the event. The objective of this study is to explain how this event affects the behavior of the subject, all this was demonstrated through the application of different techniques such as observation, interview, psychometric tests such as the PSQ that resulted in a high index and TQ that gave as an effect of General PSQ=57(medium) and Recent PSQ=83(high), thus verifying the signs and symptoms presented by the patient, using the qualitative method to carry out this study in the individual. A therapeutic scheme based on Cognitive-Behavioral Therapy (CBT) was carried out, which will help improve the well-being of the individual's life.